Compare respondents’ perceptions of the effectiveness of internal control in construction firms - Trang, To Thi Thu; Hoang, Pham Vu; Dang, Pham Van; Hau, Nguyen Van (Journal of Ecohumanism, 2024)
The following were the objectives of this study: (i) analysis and measurement of the effectiveness of internal control in construction firms in Thai Binh province, Vietnam; (ii) comparison of assessments of the effectiveness of internal control in construction firms in Thai Binh province, Vietnam, between respondents. The data used in this study are primary, including survey data obtained from the respondents. We designed a questionnaire related to the effectiveness of internal control in construction firms. We determined the observed variables (scales) of the effectiveness of internal control in construction firms based on previous studies and expert interview results. We use both qualitative and quantitative research methods, including the independent T test and ANOVA analysis. Besides, the study analyzed data for construction firms during the period 2020–2023. According to the findings of this study, three attributes of the effectiveness of internal control in construction firms in Thai Binh province were evaluated as average. All the attributes of the variables are statistically significant. There is no statistically significant difference in the effectiveness of internal control in construction firms in Thai Binh province between these different genders, ages, marriages, and job positions. This article is an academic contribution that enables understanding of the research developed and focuses on the effectiveness of internal control in construction firms in Thai Binh province, considering data from several reference research databases and survey results.